Immunomodulatory properties of cholecalciferol in rats with experimentally induced inflammation - Nina Doncheva; Anita Mihaylova; Hristina Zlatanova; Mariya Ivanovska; Delian Delev; Ilia Kostadinov (Pensoft Publishers, 2024)
The study aimed to investigate anti-inflammatory and immunomodulatory effects of cholecalciferol (vitamin D3) in rats with complete Freund's adjuvant-induced arthritis (AIA) and lipopolysaccharide (LPS)-induced inflammation. In the first experiment, rats were treated with cholecalciferol 14 days before or from the day of induction of arthritis. In the second set-up, animals received cholecalciferol for 14 days which was followed by LPS injection. TNF (tumour necrosis factor)-alpha, IL (interleukin)-1β, TGF (transforming growth factor)-β1 levels were measured by enzyme linked immunosorbent assay (ELISA). Cholecalciferol treatment reduced paw oedema and ankle joint diameter in AIA. Significantly lower IL-1β concentrations were found in cholecalciferol-treated arthritic rats. In LPS-challenged rats, cholecalciferol markedly lowered serum TNF-α, whereas an elevation in IL-1β concentrations was observed. Cholecalciferol slightly increased TGF-β1 serum concentration in arthritic rats and non-significantly reduced its level in LPS-challenged animals. Our findings showed that cholecalciferol exerts immunomodulatory properties which probably contribute to its anti-inflammatory effect.